The effect of applied direction of kinesio taping in ankle muscle strength and flexibility - Lee, Y. Y.; Chang, H. Y.; Chang, Y. C.; Chen, J. M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine the effect of applied direction of Kinesio taping (KT) in ankle range of motion and calf muscle strength. Twenty healthy subjects voluntarily participated in this study. The ankle plantar flexor muscle strength and ankle dorsiflexion ROM were assessed in knee flexion and knee extension before and after taping applied. Two applied directions, heel to posterior of knee cap (insertion to origin of calf muscles) and posterior of knee cap to heel (origin to insertion of calf muscles) were applied over both side of calf muscles, respectively. The results had not showed significantly difference in any of the results. The beneficial effects of applied direction of KT has not provided scientific evidence in this study. Future study may be able to seek other methods to identify the effect on strength or flexibility while KT applied.